THERMAL COMFORT EVALUATION OF GREEN OPEN SPACES IN NORTH AND SOUTH TELUK BETUNG, BANDAR LAMPUNG - Mida Nuraini; Rian Adetiya Pratiwi; Muhammad Saddam Ali (Lakar: Jurnal Arsitektur, 2023)
Green open space is an elongated area or polygon whose use is carried out openly and is used as a place for plants to grow, both naturally and deliberately planted, and has important functions, one of which is an ecological function. Population growth causes land conversion and environmental quality to decline, thus having a negative impact on the availability of green open space in an urban environment. Betung Bay is one of the sub-districts in Bandarlampung, an area with quite high population density and growth, so it is necessary to optimize the quality of existing green open spaces to provide benefits to the environment. This research aims to evaluate the level of thermal comfort when viewed from its ecological function and microclimate, so that recommendations for plant arrangement can be made based on the results of this evaluation. The research methods used are quantitative and qualitative with inventory stages, analysis using the Key Performance Index (KPI); Thermal Humidity Index (THI), and synthesis in the form of recommendations. Based on the results of the KPI analysis, the plants in Dipangga Park are good in terms of temperature modification with a percentage of 38% and have the lowest temperature, while the plants in Reflection Park are good in controlling humidity with a percentage of 53% and have ideal low humidity. The results of the THI analysis show that the three RTHs are included in the uncomfortable category. The recommendation from the evaluation results is to arrange vegetation by paying attention to standardization and considering the preferences of respondents.